PERANAN GURU SOSIOLOGI MEMBINA PERILAKU SISWA BERMASALAH DI KELAS XI IIS 4 SMAN 6 PONTIANAK - Ariadi, Dodi (UNIVERSITAS TANJUNGPURA, 2017)
Role of teacher as role model, motivator, and supervisor. 1) For example, the teacher of sociology is a figure that is mimicked and imitated by all the students who follow the lesson, therefore the teacher of sociology when teaching must show good behaviors that can inspire and motivate students who are learning. 2) As a motivator, a teacher should encourage students to learn earnestly, give warning to students, and instill discipline to students to be disciplined in class. In this case the role of teachers as a motivator in learning and motivated to behave well during the learning process took place. 3) Teachers as supervisors of course have the task to monitor and control the behavior of students with problems in order to continuously violate the rules of teaching and learning in the classroom. When the student's behavior deviates from the school rules then the student needs to be given advice and direction to avoid infringement.Â Keywords: Master's Role.